Model for Knowledge Management in Software Project Planning in University Research Groups - Sierra Joya, Luis Fernando; Becerra Ardila, Luis Eduardo; Diaz , Laura (TECCIENCIA, 2014)
Currently, organizations have assigned much importance to the knowledge generated inside and outside the organization, considering it a valuable asset to obtain sustainable competitive advantages and because of its influence in improving their processes, which makes it necessary to create strategies aimed at adequate knowledge management. Knowledge management plays an important role in software development organizations, given that it permits discovering new knowledge, capture it, store it, retrieve it, share it among the members of the organization, and understand it in favor of improvement in terms of costs reduction, greater precision in the definition of the scope and times planned and improvement in the quality of the project. This article presents the results of a qualitative research, which proposes a model that guides the incorporation of knowledge management onto software project planning in university research groups. Among the main results, we find as relevant the areas of scope and time management, as well as follow up and control of projects, which can be improved through the implementation of practices and tools of knowledge management like: collaborative systems, systems for documentary management, training, systems for management of lessons learnt, among others.